'Validation of ultrasound examinations performed by general practitioners'. (3rd July 2017) - Lindgaard, Karsten; Riisgaard, Lars
Abstract: Objective: The aim of this study was to evaluate the diagnostic agreement when a general practitioner and subsequently a specialist (radiologist/gynecologist) performed point-of-care ultrasound examinations for certain abdominal and gynecological conditions of low to moderate complexity. Design: A prospective study of inter-rater reliability and agreement. Setting: Patients were recruited and initially scanned in general practice. The validation examinations were conducted in a hospital setting. Subjects: A convenient sample of 114 patients presenting with abdominal pain or discomfort, possible pregnancy or known risk factors toward abdominal aortic aneurism were included. Main outcome measures: Inter-rater agreement (Kappa statistic and percentage agreement) between ultrasound examinations by general practitioner and specialist for the following conditions: gallstones, ascites, abdominal aorta >5 cm, intrauterine pregnancy and gestational age. Results: An overall Kappa value of 0.93 (95% confidence interval (CI): 0.87–0.98) was obtained. Ascites, abdominal aortic diameter >5cm, and intrauterine pregnancy showed Kappa values of 1. Conclusion: Our study showed that general practitioners performing point-of-care ultrasound examinations with low-to-moderate complexity had a very high rate of inter-rater agreement compared with specialists.